Analisis Sistem Penerapan Profit Selling pada Akad Murabahah dan Musyarakah Mutanaqisah Dalam Menyalurkan Kredit Kepemilikan Rumah (KPR) : (Studi Kasus Bank Muamalat Kc Medan Balaikota) - Kharisa Abdi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This research aims to determine the system analysis for implementing profit sales in murabahah and musyarakah mutanaqisah contracts in home ownership credit (KPR) financing in the case study of Bank Muamalat Kc Medan Balaikota. This thesis is a result that aims to find out how sales profits are applied in murabahah and musyarakah mutanaqisah contracts in home ownership credit (KPR) financing, how the comparison of sales profits in murabahah contracts and musyarakah mutanaqisah contracts, then what is the marketing strategy of Bank Muamalat KC Medan Balaikota in mortgage products. This research uses a descriptive qualitative approach method. The object of this research is Bank Muamalat Indonesia KC Medan Balaikota. Research results are determined by describing the results of interviews in the field and drawing conclusions from the results of interviews that have been conducted. This research shows that the application system for profit sales that has been implemented by Bank Muamalat KC Medan Balaikota on murabahah and musyarakah mutanaqisah contracts is in accordance with the theory reviewed based on a fixed margin and determined at the beginning. And in calculating the sales profit for each product, the lowest sales profit is from the Fix n Fix murabahah contract.